An epigenetic memory at the CYP1A gene in cancer-resistant, pollution-adapted killifish - Samantha Carrothers; Rafael Trevisan; Nishad Jayasundara; Nicole Pelletier; Emma Weeks; Joel N. Meyer; Richard Di Giulio; Caren Weinhouse (Scientific Reports)
Abstract Human exposure to polycyclic aromatic hydrocarbons (PAH) is a significant public health problem that will worsen with a warming climate and increased large-scale wildfires. Here, we characterize an epigenetic memory at the cytochrome P450 1 A (CYP1A) gene in wild Fundulus heteroclitus that have adapted to chronic, extreme PAH pollution. In wild-type fish, CYP1A is highly induced by PAH. In PAH-tolerant fish, CYP1A induction is blunted. Since CYP1A metabolically activates PAH, this memory protects these fish from PAH-mediated cancer. However, PAH-tolerant fish reared in clean water recover CYP1A inducibility, indicating a non-genetic effect. We observed epigenetic control of this reversible memory of generational PAH stress in F1 PAH-tolerant embryos. We detected a bivalent domain in the CYP1A promoter enhancer comprising both activating and repressive histone post-translational modifications. Activating modifications, relative to repressive ones, showed greater increases in response to PAH in sensitive embryos, relative to tolerant, consistent with greater gene activation. PAH-tolerant adult fish showed persistent induction of CYP1A long after exposure cessation, which is consistent with defective CYP1A shutoff. These results indicate that PAH-tolerant fish have epigenetic protection against PAH-induced cancer in early life that degrades in response to continuous gene activation.